2023
DOI: 10.1002/chem.202203097
|View full text |Cite
|
Sign up to set email alerts
|

Yolk‐shell Co3O4@Fe3O4/C Nanocomposites as a Heterogeneous Fenton‐like Catalyst for Organic Dye Removal

Abstract: The yolk-shell Co 3 O 4 @Fe 3 O 4 /C nanocomposites with Co 3 O 4 as the core, Fe 3 O 4 /C as the shell, and a cavity structure were synthesized by the hard template method. The physical and chemical properties of the composites were characterized by SEM, TEM, XRD, TGA, XPS, BET, and VSM. The specific surface area of yolk-shell Co 3 O 4 @Fe 3 O 4 /C nanocomposites is 175.9 m 2 g À 1 , showing superparamagnetic properties. The yolk-shell Co 3 O 4 @Fe 3 O 4 /C nanocomposites were used as heterogeneous Fenton cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For CFO-C and CFO-N catalysts, two broad reduction peaks are detected in the range of 275–500 °C, which may correlate with the reduction of CuO (Cu 2+ → Cu + → Cu 0 ) and the surface Fe 3+ → Fe 2+ in Fe 3 O 4 , , whereas the relatively weak peaks ranging from 600 to 800 °C may correspond to the bulk Fe 3+ → Fe 2+ and the reduction of Fe 2+ to Fe 0 . , For the CFO–C-I and CFO–N-I catalysts, an evident shift toward lower and higher temperatures occurs in the first two and the subsequent peaks, respectively, which reflects the improvement in the redox capability of Cu 2+ /Cu + and Fe 3+ /Fe 2+ , and the suppression of Fe 2+ → Fe 0 , revealing the enhancement in the complete redox cycle. In addition, the H 2 consumption increases at the initial stage (below 250 °C) for these two catalysts, accompanied by the appearance of a weak peak at approximately 180 °C (Figure e), which may be caused by the reduction of Cu 2+ at the interface in the Cu 2+ –O–Fe 3+ structure. , This further implied that the enhanced low-temperature reducibility of CFO–C-I and CFO–N-I originated from the Cu 2+ –O–Fe 3+ entity. Ultimately, the comprehensive results of Raman, XAFS, DFT calculations, O 2 -TPD, and H 2 -TPR elucidated the origin of the highly active surface O latt .…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…For CFO-C and CFO-N catalysts, two broad reduction peaks are detected in the range of 275–500 °C, which may correlate with the reduction of CuO (Cu 2+ → Cu + → Cu 0 ) and the surface Fe 3+ → Fe 2+ in Fe 3 O 4 , , whereas the relatively weak peaks ranging from 600 to 800 °C may correspond to the bulk Fe 3+ → Fe 2+ and the reduction of Fe 2+ to Fe 0 . , For the CFO–C-I and CFO–N-I catalysts, an evident shift toward lower and higher temperatures occurs in the first two and the subsequent peaks, respectively, which reflects the improvement in the redox capability of Cu 2+ /Cu + and Fe 3+ /Fe 2+ , and the suppression of Fe 2+ → Fe 0 , revealing the enhancement in the complete redox cycle. In addition, the H 2 consumption increases at the initial stage (below 250 °C) for these two catalysts, accompanied by the appearance of a weak peak at approximately 180 °C (Figure e), which may be caused by the reduction of Cu 2+ at the interface in the Cu 2+ –O–Fe 3+ structure. , This further implied that the enhanced low-temperature reducibility of CFO–C-I and CFO–N-I originated from the Cu 2+ –O–Fe 3+ entity. Ultimately, the comprehensive results of Raman, XAFS, DFT calculations, O 2 -TPD, and H 2 -TPR elucidated the origin of the highly active surface O latt .…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, the relatively weak diffraction peaks that correspond to the tetragonal spinel Fe 3 O 4 (JCFDS No. 19–0629) are observed at 18.2, 30.1, 57.1, and 62.7° even though the main peak at 2θ of 35.5° may overlap with that of CuO . The near-identical XRD patterns and no peak shift indicated that CuO and Fe 3 O 4 coexist in all catalysts, and the distinction in crystal structure could be neglected.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Its excellent stability properties do not allow it to auto‐degrade naturally. So, photocatalytic degradation is one of the highly acceptable green strategies for the mineralization of these industrial dye wastewater, using a stable, non‐toxic, economic, and visible light active heterogeneous photocatalyst through advanced oxidation and reduction processes [3–5] . The reactive species such as superoxide radical (O 2 − ), hydroxyl radical (⋅OH), and hole (h + ) produced in this process have a major role in the degradation of dyes, with CO 2 and H 2 O as the end product [6–11] …”
Section: Introductionmentioning
confidence: 99%
“…So, photocatalytic degradation is one of the highly acceptable green strategies for the mineralization of these industrial dye wastewater, using a stable, non-toxic, economic, and visible light active heterogeneous photocatalyst through advanced oxidation and reduction processes. [3][4][5] The reactive species such as superoxide radical (O 2 À ), hydroxyl radical ( * OH), and hole (h + ) produced in this process have a major role in the degradation of dyes, with CO 2 and H 2 O as the end product. [6][7][8][9][10][11] Among transition metal-based photocatalysts, 2D Layered photocatalysts emerged as a new class of materials originating from their distinct structures, giving rise to the anisotropy required for charge separation in photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%